Initiation of simian virus 40 DNA synthesis in vitro. - Bullock, P A (1991)
Simian virus 40 (SV40) T antigen can efficiently initiate SV40 origin-dependent DNA synthesis in crude extracts of HeLa cells. Therefore, initiation of SV40 DNA synthesis can be analyzed in detail. We present evidence that antibodies which neutralize proliferating cell nuclear antigen (PCNA) inhibit but do not abolish pulse-labeling of nascent DNA. The lengths of DNA products formed after a 5-s pulse in the absence and presence of anti-PCNA serum averaged 150 and 34 nucleotides, respectively. The small DNAs formed in the presence of anti-PCNA serum underwent little or no increase in size during further incubation periods. The addition of PCNA to reaction mixtures inhibited with anti-PCNA serum largely reversed the inhibitory effect of the antiserum. The small nascent DNAs formed in the presence or absence of anti-PCNA serum products arose from the replication of lagging strands. These results suggest that a PCNA-dependent elongation reaction participates in the synthesis of lagging strands as well as leading strands. We also present evidence that in crude extracts of HeLa cells, DNA synthesis generally does not initiate within the core origin. Initiation of DNA synthesis outside of a genetically defined origin region has not been previously described in a eukaryotic replication system but appears to be a common feature of initiation events in many prokaryotic organisms. Additional results presented indicate that in the absence of nucleoside triphosphates other than ATP, the preinitiation complex remains within or close to the SV40 origin.